Energy Profiling and Building Energy Index for Residential College of Government University - Nur Syafiqah Adha Narrudin; Mohd Azahari Razali; Winardi Sani; Juntakan Taweekun; Mohd Azni Md Kasim (International Journal of Integrated Engineering, 2025)
Building energy profiling involves analyzing and understanding energy consumption across various systems within a building. The growing number of students residing in UTHM’s residential college has resulted in increased energy consumption, which leads to energy waste and higher operational expenses. For this study, Tun Dr. Ismail Residential College (KKTDI) was selected to examine its energy consumption patterns and the breakdown of energy usage and also determine the Building Energy Index (BEI). The energy profiling process at UTHM Residential College comprised several stages: selecting a suitable building for the audit, collecting both desktop and field data, analyzing energy consumption patterns, identifying the breakdown of energy usage within the building systems, and calculating the BEI for KKTDI Residential College. The results reveal that KKTDI displays a varied energy consumption pattern throughout 2023. Weekly energy profiling indicates that energy consumption on weekdays is slightly higher than on weekends. In contrast, daily energy consumption patterns show that energy usage remains stable during weekdays compared to weekends. The analysis of energy usage within the building systems reveals that general equipment is the largest contributor to energy consumption, followed by lighting and the Air Conditioning and Mechanical Ventilation (ACMV) system. The BEI for KKTDI is lower than the MS1525:2019 BEI standard, indicating that the residential college uses less energy to meet its operational requirements. These findings emphasize the value of analyzing energy utilization in buildings to identify consumption patterns and assess building efficiency. This data can be leveraged in the future to locate inefficiencies and pinpoint potential energy savings throughout the building.